The Assessment of Mutual Investment Activity of the EAEU Member Countries - Avagyan, Misak (Bulletin of Yerevan University G: Economics, 2018)
The effectiveness of integration processes is conditioned by the free movement of not only of goods and services but also of capital and labor between countries of participants. For the further success of the Eurasian Economic Union, it is also important to ensure the active movement of all production factors. The article presents the main features of attracting investments by the EAEU member states, as well as the dynamics of mutual investments within the Union and the assessment of their activity